Cystic echinococcosis in Mundari tribe-members of South Sudan. (1st September 2013) - Stewart, Barclay T; Jacob, Joseph; Finn, Timothy; Lado, Mounir; Napoleon, Robert; Brooker, Simon; Sidhu, Paul S; Kolaczinski, Jan
Abstract : Many neglected tropical diseases, including the zoonotic disease cystic echinococcosis (hydatidosis), are endemic to East Africa. However, their geographical distribution is heterogenous and incompletely characterized. The aim of this study was to determine if Mundari pastoralists harbor endemic human hydatidosis. The survey was conducted in cattle camps randomly selected from accessible sites provided by officials in Terekeka, South Sudan. Following informed consent, a questionnaire collected demographic data and hydatid exposure risk. A systematic sonographic abdominal exam was performed using General Electric's LOGIQ Book XP with a 3C-RS 2-5 MHz curvilinear transducer. Six hundred and ten individuals were screened from 13 camps. Four infections were identified, all in women. The prevalence of abdominal hydatid disease in the Mundari tribe-members in cattle camps was 0·7% and all individuals reporting at least one high-risk exposure to hydatid disease. Cystic echinococcosis is endemic among Mundari pastoralists; however, it would appear to be less endemic than in neighboring tribes.